2021
DOI: 10.3390/pathogens10030287
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Shedding in Milk and Molecular Typing of Strains Infecting Dairy Cows in Greece

Abstract: Ruminants are considered the commonest animal reservoir for human infection of Coxiella burnetii, the Q fever causative agent. Considering the recently described importance of human Q fever in Greece, we aimed at providing the first comprehensive direct evidence of C. burnetii in dairy cows in Greece, including the genetic characterization of strains. The 462 examined dairy farms represented all geographical areas of Greece. One bulk tank milk sample was collected from every farm and tested for the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Dobos et al ( 11 ) tested 370 dairy cattle herds from six countries of the Central and Eastern European region and detected C. burnetii shedding in 44.05%. The study performed by Kalaitzakis et al ( 26 ) in Greece showed 33.8% prevalence, whereas 10.7% of herds were PCR-positive in Latvia ( 7 ).…”
Section: Discussionmentioning
confidence: 96%
“…Dobos et al ( 11 ) tested 370 dairy cattle herds from six countries of the Central and Eastern European region and detected C. burnetii shedding in 44.05%. The study performed by Kalaitzakis et al ( 26 ) in Greece showed 33.8% prevalence, whereas 10.7% of herds were PCR-positive in Latvia ( 7 ).…”
Section: Discussionmentioning
confidence: 96%
“…In the present investigation, 57.61% of all positive milk samples had 3.0 log10 DNA copies/ml, and therefore should be recognised as strongly positive. Cattle can be asymptomatic and shed C. burnetii in milk more often than goats and sheep, and for longer periods (Rodolakis et al, 2007); therefore, BTM samples provide suitable material for detecting cattle sheds with active C. burnetii milk shedders (Kalaitzakis et al, 2021). The shedding pattern in cattle can be persistent, sporadic or intermittent (Guatteo et al, 2007), but other routes of shedding have to be assessed as well (vaginal mucus, faeces) to estimate the disease prevalence more accurately (Guatteo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…), cases of Q fever are most heavily clustered in regions containing livestock and farm animal processing centers [115]. Although the reservoir for this bacterium is expansive, comprising various animals, livestock are the most common source implicated in transmission to humans [37]. Inhalation of aerosolized bacteria from livestock birthing or still birth fluid, vaginal mucus, feces, and other secretions is the most common form of spread [116][117][118].…”
Section: Coxiella Burnetiimentioning
confidence: 99%
“…In contrast, Anaplasma and Ehrlichia are predominantly found in the United States and are transmitted via numerous tick species [35,36]. C. burnetii, although found globally, is endemic to the Mediterranean region and is commonly spread via livestock secretions [37]. However, recent evidence indicates that ticks may serve as a vector of transmission [38][39][40].…”
Section: Introductionmentioning
confidence: 99%